Aproximaciones al marxismo latinoamericano Teoría, historia y política - Cabaluz, Fabián (Ariadna Ediciones, 2021)
This book is an excellent contribution to the knowledge of Latin American Marxism, as a set of theoretical reflections committed to the subaltern classes and popular struggles. The authors discussed by Fabián Cabaluz and Tomas Torres are very different, due to their national origin, their thematic approaches, and their political orientations: René Zavaleta Mercado, Álvaro García Linera, Aníbal Quijano and Enrique Dussel. However, as these essays show, they are part of a heterodox, heretical, anti-dogmatic Latin American Marxism, which tries to create new intellectual concepts and tools to understand Latin America - in opposition to another type of Marxism, which only seeks to apply the models theorists and politicians formulated by the Comintern, or by the Stalinist USSR (from the foreword by Michel Löwy)